2002
DOI: 10.2307/3071864
|View full text |Cite
|
Sign up to set email alerts
|

Drought Cycles and Landscape Responses to past Aridity on Prairies of the Northern Great Plains, USA

Abstract: Widespread drought is among the most likely and devastating consequences of future global change. Assessment of drought impacts forecast by atmospheric models requires an understanding of natural drought variability, especially under conditions more arid than today. Using high-resolution lake-sediment records from the northern Great Plains, we show pronounced 100-to 130-yr drought cycles during the arid middle Holocene (8000 calendar yr BP). During drought phases, grass productivity declined, erosion and forbs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 112 publications
(64 citation statements)
references
References 27 publications
4
60
0
Order By: Relevance
“…Following the drought, perennials (mostly C 4 shortgrass species, e.g., buffalo grass and blue grama) quickly regained their dominance at the expense of weedy annuals, marking the shift to more stable conditions (Weaver and Flory, 1934;Albertson and Weaver, 1946). These historical observations and the findings of Clark et al (2002) support our interpretation of increased C 3 vegetation during periods of drought and Bignell Loess deposition throughout the Holocene.…”
Section: Downloaded By [University Of Windsor] At 01:48 18 November 2014supporting
confidence: 75%
See 3 more Smart Citations
“…Following the drought, perennials (mostly C 4 shortgrass species, e.g., buffalo grass and blue grama) quickly regained their dominance at the expense of weedy annuals, marking the shift to more stable conditions (Weaver and Flory, 1934;Albertson and Weaver, 1946). These historical observations and the findings of Clark et al (2002) support our interpretation of increased C 3 vegetation during periods of drought and Bignell Loess deposition throughout the Holocene.…”
Section: Downloaded By [University Of Windsor] At 01:48 18 November 2014supporting
confidence: 75%
“…Pollen evidence from the Great Plains indicates that episodic drought was common during the Holocene, signaled by increased pollen from disturbance indicators, e.g., Chenopodeaceae-Amarathanceae (Cheno Am) or Ambrosia type pollen, and fluctuating water levels (Watts and Wright, 1966;Grüger, 1973;Fredlund, 1995;Loope and Swinehart, 2000;Grimm, 2001;Clark et al, 2002). Arbogast and Johnson (1998) analyzed faunal and floral remains gathered in south-central Kansas and concluded that the late-Wisconsin environment was cooler and more moist than the Holocene.…”
Section: Evidence For Ecosystem and Climate Change In The Central Grementioning
confidence: 96%
See 2 more Smart Citations
“…Enhancement ET o may have negative implications on ecosystem and agriculture, like crop growth in the Haihe River Basin which is an important grain production base in eastern China (Wang et al, 2011). Moreover, increased aridity has the potential impact on grassland composition and productivity (Clark et al, 2002), and the forest growth would decline and mortality rates may increase substantially response to rising aridity (Williams et al, 2010). Therefore, ecosystem across the eastern China would be affected adversely by future warming and increasing aridity.…”
Section: Discussionmentioning
confidence: 99%